2016
DOI: 10.1109/tns.2016.2524625
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Radiation Sensor Aspects of $\text{Er}_2$$\text{O}_3$ MOS Capacitors under Zero Gate Bias

Abstract: The aim of the present study is to investigate the usage of Erbium Oxide (Er2O3) as a gate dielectric in MOS-based radiation sensors. Er2O3 thin films were deposited on a p-type Si (100) substrate via RF magnetron sputtering and were annealed at 500 • C under N2 ambient. The structural properties of the Er2O3 thin films were determined via XRD, FTIR, and AFM analyses. The Erbium silicate formation was not observed in the XRD and FTIR spectra. The roughness root-mean-square was measured as 16.4 nm by the AFM an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 67 publications
1
8
0
1
Order By: Relevance
“…As a result of the interaction of a typical MOS capacitor with radiation, the flat band and mid-gap voltages are expected to shift to the left compared to non-irradiated electrical characteristics due to the low mobility of positive charges with respect to negatives and the expected further trapping within the structure. Although the sensitivity of the MOS capacitor produced with Er2O3 film annealed at 500 o C is higher than many high-k based devices, a bidirectional shift in C-V curve was observed [7]. Another rare earth oxide Yb2O3 was studied in the amorphous structure and the C-V curve shifted continuously to the left with increasing the dose, as expected, indicating that positive charges were more trapped in the structure than the negative ones [6].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…As a result of the interaction of a typical MOS capacitor with radiation, the flat band and mid-gap voltages are expected to shift to the left compared to non-irradiated electrical characteristics due to the low mobility of positive charges with respect to negatives and the expected further trapping within the structure. Although the sensitivity of the MOS capacitor produced with Er2O3 film annealed at 500 o C is higher than many high-k based devices, a bidirectional shift in C-V curve was observed [7]. Another rare earth oxide Yb2O3 was studied in the amorphous structure and the C-V curve shifted continuously to the left with increasing the dose, as expected, indicating that positive charges were more trapped in the structure than the negative ones [6].…”
Section: Introductionsupporting
confidence: 59%
“…In this context, the dielectrics such as Hf-based oxides, rare earth oxides were studied and the sensitivities of the some high-k MOS capacitors were found to be higher to lower dose than SiO2-based MOS device [6]- [9]. One of the most notable of these is the MOS devices based on Er2O3, which has a sensitivity of 61 mV/Gy in the dose range of 16-76 Gy [7]. As a result of the interaction of a typical MOS capacitor with radiation, the flat band and mid-gap voltages are expected to shift to the left compared to non-irradiated electrical characteristics due to the low mobility of positive charges with respect to negatives and the expected further trapping within the structure.…”
Section: Introductionmentioning
confidence: 99%
“…However, the post deposition annealing process improves the interface quality and it is possible to fabricate the RadFET with thinner gate oxide by high-k dielectrics due to the larger charge storage capacity of the high-k MOS structure compared to the device with SiO2 [20][21]. On the other side, some experimental studies on the MOS capacitors having the oxide with high-k dielectric have shown that their responses to 60 Co gamma source are higher than traditional MOS capacitor with SiO2 gate oxide [22][23][24]. There are also studies showing that MOS capacitors with different dielectrics are less sensitive to radiation compared to the structure with SiO2 [25][26].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the ever-smaller size of the microelectronic device, a thinner SiO2 layer is placed on the MOS-based structures, which lead to an increase in the leakage current of the transistor. On the other hand, alternative gate oxide layers are also needed to improve the sensitivity of MOS-based radiation sensors in low doses (< 10 mGy) [1,2]. For these reasons, the researchers have begun to investigate the alternative materials to be used as gate oxide layer to solve these problems, and the studies have focused on the high-k dielectrics with the high charge storage capacity in recent years.…”
Section: Introductionmentioning
confidence: 99%